Conversaçiones de Música a finals del segle XVI: el cas de l'acadèmia de Joan de Borja i Castro. - ESCRIVÀ-LLORCA, FERRAN (Scripta, 2017)
This work is part of the research on The Court of Habsburg in Modern Era. The study of music academies is not quite known. From few works on literary academies, this article will focus on the music academy that of Juan de Borja i Castro hold in Madrid. In this way, if the courtly literary patronage is already an issue with multiple variants, the approach to other artistic activities, such as the music, it is even more. In the following pages, it will delve into the various aspects of erudition of Juan de Borja with the thread of the academies, as a centre of intellectual, creative and cultural promotion and personal. Some of the most important composers of the Iberian World of that time, such as Francisco Guerrero or Tomás Luis de Victoria, were involved in this academy. The article aims to show the relevance of this cenacle as a focal point of the musical patronage in the last decades of the 16th century Spain.